Diffraction efficiency and dielectric relaxation properties of nickel phthalocyanine doped nematic liquid crystal - Köysal, O; Okutan, A; Durmus, M; Yakuphanoğlu, Fahrettin; San, SE; Ahsen, V (Elsevier Science Sa, 2006)
The formation of the photoinduced grating and dielectric properties of a nematic liquid crystal doped by nickel plathalocyanine have been investigated to enhance the optical and electrical properties of the system studied by dielectric spectroscopy and diffraction grating measurements. Accessible diffraction efficiency is 7% under the optimum circumstances and analyzed results establishes a better reorientation panorama in the sense that NiPc component improves efficiency. Photoinduced refractive index change Delta n was determined by two-wave mixing method. The addition of NiPc to E7 enhances the diffraction efficiency and refractive index change of the LC samples. The dielectric parameters and relaxation properties of nickel phthalocyanine (NiPc) doped E7 and pure E7 liquid crystal have been investigated. Dielectric anisotropy (Delta epsilon) property of the LCs changes from the positive type to negative type and dielectric anisotropy values increase with NiPc. The complex dielectric dispersion curves of the LC samples were analyzed Cole-Cole relation and the relaxation process obeys the Debye type relaxation. Consequently, NiPc dopant changes the refractive index, diffraction efficiency, dielectric anisotropy and relaxation parameters of E7/NiPc LC. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: liquid crystals; dielectric anisotropy; diffraction efficiency